Corrosion behavior of ZrB2–SiC–Graphite ceramic in strong alkali and strong acid solutions. Issue 2 (1st February 2016) - Wang, Zhi; Zhao, Quanyue; Jing, Li; Wu, Zhanjun; Sun, Ximiao
Abstract: The corrosion behavior of the ZrB2 –SiC–Graphite (ZrB2 –SiC–G) ceramic in strong alkali and strong acid solutions containing different aggressive anions such as chlorides and sulfates after immersion for 1 h, 3 day and 12 day was investigated. The microstructure of specimen corroded for 45 day indicated that ZrB2 –SiC–G ceramic underwent an electrochemical corrosion attack on the ZrB2 phase and SiC phase, while graphite exhibited chemical inertness. In strong alkaline solution, the corrosion behavior mainly lies on SiC phase, while in strong acid solution the corrosion behavior mainly lies on ZrB2 phase. Otherwise, at the initial corrosion attack, the SiC phase easily underwent corrosion attack in strong alkaline solution, so ZrB2 –SiC–G ceramic had greater corrosive resistance in strong acid solution than that in alkaline solution.